Comparing Sports IoT Healthcare Devices and e-Health Literacy and Awareness among College Students: Pre-and Post-COVID-19 Perspectives - Chungyun Kim, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study investigated the difference between sports major college students' perception of using IoT healthcare devices and e-health literacy before and after COVID-19. A quantitative research questionnaire was distributed randomly among 600 sports college students majoring in sports in metropolitan and non-metropolitan universities in Korea. The study's findings show a significant difference in perception of using IoT healthcare devices and e-health literacy before and after COVID-19. Secondly, before COVID-19, the perception of the use of IoT healthcare devices showed significant differences by grade. On the other hand, functional e-health literacy, communication e-health literacy, and critical e-health literacy showed significant differences by grade. Third, there was no significant difference in perception of the use of IoT healthcare devices by grade after COVID-19. Conversely, functional e-health literacy, communication e-health literacy, and critical e-health literacy showed significant differences by grade. Fourth, before COVID-19, there were statistically significant differences in perceptions of using IoT healthcare devices in local cars. However, there was no statistically significant difference in terms of e-health literacy. Fifth, there was no statistically significant difference in regional differences between the metropolitan and non-metropolitan areas after COVID-19. This study showed the differences between COVID-19 and after COVID-19 by comparing the high level of awareness of using IoT healthcare devices and e-health literacy of sports college students, which will foster talented people who can demonstrate professionalism in the sports field.